Kehidupan Sosial Ekonomi di Nagari Parik Malintang Sebagai Ibukota Padang Pariaman (2008-2020) - Miftahul Khairatul Syur'an; Najmi Najmi (Jurusan Sejarah FIS UNP, 2022)
Nagari Parik Malintang has been governmental centre since 2008 and brings many changes include socio-economical life there. This paper describe these changes and interferences from Regency’s government of Padang Pariaman, using historical method. Results show that establishing Nagari Parik Malintang as a new capital of Padang Pariaman have brought great influences for socio-economical activities there. Eace year an increase occurs from the economic sector, marked by increase in income for the society, as this economic increase has an impact on the social level of the community. Attentions from the government to the development and progress of Parik Malintang can be seen from the regional assistance to reduce poverty, the 2009 earthquake disaster assistance, the development of basic, physical needs services, empowerment and community development, as well as compensation related to the construction of the new capital.